HAK PEREMPUAN MENIKAH TANPA WALI DALAM PANDANGAN IMAM SYAFIâ€™I DAN IMAM JAâ€™FARI - Ari, M. Khoirul Hadi al-Asy; Aini, Adrika Fithrotul (Musawa Jurnal Studi Gender dan Islam, 2015)
A Womanâ€™s Right to Marry without a Guardian According to Imam Syafiâ€™i and Imam Jaâ€™Fari To marry without a guardian and the issue of the marriage guardian are legal marriage issues that alwaysÂ  arouse debate among Muslims. In classical literature, â€œit seemsâ€ women do not have the right to marry without a guardian. This paper examines whether women have the right to marry without a guardian and theÂ  issue of guardians. This matter not explained explicitly or in detail by the Prophet resulting in a multiplicityÂ  of interpretations. Religious leaders and schools of thought, as well as the State, discuss and examine these issues from a variety of perspectives. This paper explains the view of Imam Shafiâ€™i and Iman Jaâ€™fari, based on content analysis ond library-based research. This study looks firstly at patterns of thought and socio-cultural life according to Imam Shafiâ€™i and Imam Jaâ€™fari. Secondly, it discusses their views on the womenâ€™s right to marry without a guardian. Lastly, it explores the implications of their thought on the practice of women marrying without a guardian in Indonesia.